Serum placental growth factor in late first trimester of pregnancy for prediction of preeclampsia in primigravida - a case control study - Agarwal, Rachna; Chaudhary, Shweta; Kar, Rajarshi; Radhakrishnan, Gita; Sharma, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: We studied the correlation of serum PLGF levels at 11-14 weeks in primigravida for prediction of future preeclampsia in a prospective nested case control study and estimated the critical levels of PLGF for possible use as screening test. Methods: Subjects with preeclampsia/gestational hypertension were taken as cases with an equal number of controls. Results: Out of 300 participants, final analysis was possible in 291 subjects. Thirty five were cases; two had early PE, 15 late PE and 18 had GH. PLGF level was lower in cases (20 pg/ml) compared to controls (79 pg/ml). PLGF was significantly lower in PE cases (15 pg/ml) compared to GH cases (34 pg/ml). PLGF had maximum area under the ROC curve (AUC) for PE with value of 0.867. Further, late PE had more AUC (0.853) as compared to GH (0.759). The cut off value for prediction of PE was found to be <30 pg/ml with 88.2% sensitivity and 71.4% specificity. Conclusions: PLGF levels were significantly lower in first trimester serum samples of subjects who later developed either preeclampsia or gestational hypertension. PLGF had better detection rate for PE and late PE as compared to GH.